KEANEKARAGAMAN TUMBUHAN PENYEMBUH LUKA DI LINGKUNGAN GETAP, KECAMATAN CAKRANEGARA, KOTA MATARAM - Siratul Aini; Slamet Mardiyanto Rahayu (Nusadaya Journal of Multidiciplinary Studies, 2025)
Getap is a neighborhood in Cakranegara District, Mataram City. This study aims to determine the diversity of wound-healing plants in Getap. Based on the research, two species have been identified as beneficial for wound healing: Kalanchoe pinnata and Aloe vera.